2020
DOI: 10.1103/physrevresearch.2.023006
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity due to cooperation of electron-electron and electron-phonon interactions at quarter filling

Abstract: We present the results of Quantum Monte Carlo calculations for a two dimensional frustrated Hubbard model coupled to bond phonons. The model is known to have a d-wave superconducting ground state in the limit of large phonon frequency for sufficiently strong electron-phonon coupling. In the absence of electron-phonon coupling the Hubbard interaction U enhances superconducting pairing in the quarter-filled (density ρ = 0.5) band. We show here that at ρ = 0.5 electron-electron and electron-phonon interactions co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…DMRG calculations on a width-three triangular lattice found evidence for p-wave and d-wave SC in the density range 0.40∼0.65 [58], which would appear to agree with the conclusion from the previous work [41]. Additionally, electron-electron and electron-bond phonon interactions act cooperatively at this bandfilling to enhance superconducting pair correlations, even as they compete with one another at all other fillings [59]. These results are encouraging and suggest further research along this direction.…”
Section: Discussionsupporting
confidence: 88%
“…DMRG calculations on a width-three triangular lattice found evidence for p-wave and d-wave SC in the density range 0.40∼0.65 [58], which would appear to agree with the conclusion from the previous work [41]. Additionally, electron-electron and electron-bond phonon interactions act cooperatively at this bandfilling to enhance superconducting pair correlations, even as they compete with one another at all other fillings [59]. These results are encouraging and suggest further research along this direction.…”
Section: Discussionsupporting
confidence: 88%
“…Calculations on an anisotropic triangular lattice [40] as well as on κ-lattices [41,55] have indeed found that superconducting pair correlations are enhanced by the Hubbard U uniquely at 1 4 -filling. Additionally, electron-electron and electron-bond phonon interactions act co-operatively at this bandfilling to enhance superconducting pair correlations, even at they compete with one another at all other fillings [56]. These results are encouraging and suggest further research along this direction.…”
Section: Discussionmentioning
confidence: 63%
“…According to atomic configuration analysis in Figure b, under the nonequilibrium condition (low source concentration), the B and N atom preferential growth direction would deviate from the lowest barrier B-terminated (100) direction (3-fold symmetry) to the high barrier B–N armchair edge (110) direction (6-fold symmetry), forming the ideal 2D Koch snowflakes (Figure d). In addition, in critical phenomena, e.g., superconductivity , or bacterial collective motion patterns, interactions between agents (electrons and bacteria) play a critical role in their emergent behaviors. Similar to the above phenomenon, the exact self-similar Koch curve formation in this work is inextricably linked to the asymmetric interaction introduced by the mirror symmetry of the h-BN armchair edge of the growth front (Figure b), which could facilitate long-range correlations of atomic reaction-diffusion processes (i.e., trigger the KPZ interaction).…”
mentioning
confidence: 99%